Blockchain in education: studying smart contracts to create a decentralized system - Koshkinbayeva, B.; Kalpeyeva, Z. (Харківський національний автомобільно-дорожній універститет, 2024)
Recently, blockchain technology has been actively studied and used by both researchers and practitioners. This is due to its unique features, such as decentralization, security, reliability, and data integrity. The article is devoted to the possibility of introducing blockchain technology into the educational environment through smart contracts. To achieve this goal, the following tasks were set: to study blockchain technologies for their applicability in the educational environment; to justify the need for using smart contracts in the educational process; to develop an algorithm for implementing smart contracts for storing educational information and using it for further analysis. The Ethereum platform was chosen for the development of smart contracts. The program code of the smart contract was compiled in the Remix compiler.
Keywords: blockchain technology in education; smart contract; decentralized systems; blockchain technology; Ethereum Virtual Machine( EVM); Remix IDE.